Salinity stress resistance of durum wheat (Triticum durum) enhanced by fungi - Kouadria, Rabiaa; Bouzouina, Mohammed; Azzouz, Redouane; Lotmani, Brahim (International Journal of Biosciences, 2018)
Endophytic fungi are known for their biotic and abiotic resistance. We evaluated the ability of beneficial fungus to overcome salt stress. Fungi strains: Alternaria chlamydospora, Embellisi aphragmospora, Phoma betae, Fusariume quseti, Fusarium graminearum and Chaetomium coarctatum were tested for their ability to improve durum wheat germination under salinity stress conditions (0, 400, 600 and 800meq/l NaCl). Germination, radicle and coleoptile growths were inhibited in high salinity exposed durum wheat seeds, while fungal strains × salinity interaction significantly enhanced germination and growth of durum wheat. The highest germination percentage was showed by Alternaria chlamydospora under salt stress conditions (400, 600 and 800meq/L).
Keywords: Salinity; Endophytic fungi; Germination; Durum wheat